Opportunities and Challenges of the Merdeka Curriculum in the Islamic Religious Education Subject at SMA Negeri 1 Sakra, East Lombok - Rumawang, Rumawang; Ansori, Muhammad Zainul; Armawan, Armawan; Jamaludin, Jamaludin; Irrubai, Moh. Liwa (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
Education in Indonesia is undergoing significant transformation in tandem with technological advancements, with the Merdeka Curriculum emerging as a response to the demands of the modern era, particularly in the context of Industry 4.0. This curriculum introduces flexibility and innovation in learning approaches but also encounters challenges such as resource limitations and the necessity for teacher training. At SMA Negeri 1 Sakra in East Lombok, the implementation of the Merdeka Curriculum since the 2022/2023 academic year has presented opportunities for more varied and inclusive teaching methods, particularly in Islamic Religious Education (PAI), while also confronting challenges in balancing theological and practical aspects.This research aims to explore the opportunities and challenges of the Merdeka Curriculum within the Islamic Religious Education subject at SMA Negeri 1 Sakra, East Lombok Regency. Utilizing a qualitative approach with a descriptive naturalistic method, the study focuses on direct observation and a holistic understanding of the phenomena at SMA Negeri 1 Sakra, East Lombok. Data collection is conducted through observation, interviews, and documentation, employing interactive analysis based on the Miles and Huberman model to examine the implementation of the Merdeka Curriculum.The findings of this study reveal that the opportunities perceived by SMA Negeri 1 Sakra, East Lombok, after implementing the Merdeka Curriculum include enhanced enthusiasm among educators to develop their capacities, increased student engagement and activity in the classroom, and the school's ability to cultivate a learning ecosystem that is more student-centered. However, the school also faces challenges, such as the need to shift the mindset of both teachers and students, the task of harmonizing diverse Islamic values among students and teachers, the difficulty of creating enjoyable and high-quality learning experiences, and the issue of resource constraints.